2011
DOI: 10.5138/ijdd.2010.0975.0215.03059
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Characterization of Magnetic Methyl Methacrylate Microspheres Loaded with Indomethacin by Emulsion Solvent Evaporation Technique.

Abstract: Magnetic nanoparticles encapsulated in Methyl methacrylate (Eudragit L-100) microspheres containing Indomethacin drug were prepared and their detailed structural and magnetic characteristics were studied. Iron oxide nanoparticles were obtained by chemical coprecipitation of Fe(II) and Fe(III) salts and stabilized with tetra-methyl ammonium hydroxide. Microspheres were prepared by solvent evaporation technique. We characterized the magnetic microspheres in terms of morphology, composite microstructure, size and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 26 publications
(31 reference statements)
0
5
0
Order By: Relevance
“…Based on a review of previous literature combined with our results, we would entertain a notion that it is of key importance to tune the valence fluctuation of iron ions for the synthesis of greigite. A desirable route is using Fe 2+ and Fe 3+ with a stoichiometrical ratio of 1:2 [30,31] , but it still needs deliberately designed strategies. To simplify the experimental protocol, a single iron precursor is often preferred.…”
Section: Fes H S Fes Hmentioning
confidence: 99%
“…Based on a review of previous literature combined with our results, we would entertain a notion that it is of key importance to tune the valence fluctuation of iron ions for the synthesis of greigite. A desirable route is using Fe 2+ and Fe 3+ with a stoichiometrical ratio of 1:2 [30,31] , but it still needs deliberately designed strategies. To simplify the experimental protocol, a single iron precursor is often preferred.…”
Section: Fes H S Fes Hmentioning
confidence: 99%
“…The saturation magnetization of Fe 3 O 4 particles at 2500 G were found to be 2.4 emu/g, which are in good agreement with magnetic data reported on magnetite. Varma et al, 32 reported the saturation magnetization of chemically synthesised Fe 3 O 4 particles at 8000 G was found to be 2.4 emu/g. Very lower i.e.…”
Section: Characterization Of Magnetitementioning
confidence: 99%
“…Leukemia is a cancer of the white blood cells and bone marrow. Magnetic microspheres were formulated by 3 2 factorial designs [1]. Thus, a formulation, that is, magnetic microspheres was prepared for cytarabine.…”
Section: Introductionmentioning
confidence: 99%